Handbook of research on mass shootings and multiple victim violence - Crews, Gordon A. (Information Science Reference, 2020)
""This book examines a variety of topics that impact the serious problem of mass shootings, including, but not limited to factors such as mental illness, access to guns, revenge for bullying, copycat incidents, characteristics of the shooters, and characteristics of the victims"- Resumé vydavatel
Keywords: masové vraždy; střelba; násilné trestné činy; mass murder; shooting; violent crimes; elektronické knihy; příručky; electronic books; handbooks and manuals